STRATEGI MENINGKATKAN KEPATUHAN PAJAK REKLAME DENGAN PENDEKATAN COMPLIANCE MODEL - Wijayanah Wijayanah; Basuki Basuki (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2021)
This study aims to describe the implementation of compliance strategies in revenue agencies using the compliance model approach to improve advertising tax compliance. The research data were collected by interview, observation and document collection. This research is a descriptive qualitative research with a case study approach. Data analysis was performed using qualitative techniques, consisted of 3 stages, namely data reduction, data display, and conclusion drawing. The results of the study provide empirical evidence that compliance strategy with a compliance model approach that is implemented comprehensively and adequately can increase taxpayer compliance. The strategy implemented includes providing ease of compliance, providing assistance to comply, taking deter by detection and use full force of the law. Its combines effective prevention strategies and credible enforcement, making easier for taxpayers who are committed to comply and take firm action against taxpayers who do not comply. Implementation of compliance strategy requires support of facilities and infrastructure, competent human resources, tax authorities commitment, laws and regulations as a basis for implementation and support from other agencies in law enforcement efforts. The results of this study can become a reference for policy makers in developing future compliance strategies to achieve voluntary compliance in a sustainable manner.